Wind, coal, and copper: the politics of land grabbing, counterinsurgency, and the social engineering of extraction. Issue 4 (18th May 2020) - Dunlap, Alexander
ABSTRACT: The multiplicity of violent techniques employed to impose land control and extraction remains under acknowledged. This article reviews research conducted between the years 2014 and 2018 and draws on three case studies: wind energy development in Mexico, coal mining in Germany, and copper mining in Peru. The idea of 'engineering extraction' is advanced through counterinsurgency to acknowledge the extent of extractive violence, arguing that the term 'land grabbing' is indeed a more appropriate term than 'land deals'. Engaging with the land grabbing literature, the three cases seek to advance discussions around 'the political reactions "from below"' by emphasizing 'insurrectionary' positions with resistance movements fighting land deals and extractive projects. This is followed by offering a typology of 'hard' coercive techniques and 'soft' technologies of social pacification that surfaced in each case. The conclusion reflects on the social technologies of resource extraction, recognizing how social discord, ecological and climate crises are engineered and enforced.